Cure Kinetic of Castor Oil-Based Polyurethane - Milanese, Andressa Cecilia [UNESP]; Hilario Cioffi, Maria Odila [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Shigue, Carlos Yujiro [UNESP] (Wiley-Blackwell, 2011)
This research presents the kinetic studies on the cure reactions of a new material, castor oil-based polyurethane resin. Thermal analysis by isothermal differential scanning calorimetry was used, as a variety of factors affect its cure, including formulation and polymerization process. The kinetic reaction of this catalyzed system is described by nth order equation. Castor oil, a vegetable triglyceride, was reacted with methylene diphenyl 4,4'-diisocyanate to produce an elastomeric matrix. The objective of this research is thermal characterization of new polyurethane that is less aggressive to humans and environment; therefore, castor oil used on the synthesis is derived from a natural and renewable resource. The activation energy measured for the castor oil-based polyurethane resin studied in this work was about 56 kJ/mol. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 122: 3168-3171, 2011
Keywords: activation energy; curing of polymers; polyurethane; differential scanning calorimetry; kinetics